Case Report: Baló's Concentric Sclerosis-Like Lesion in a Patient With Relapsing-Remitting Multiple Sclerosis Treated With Dimethyl Fumarate - Kania, Karolina; Ambrosius, Wojciech; Kozubski, Wojciech; Kalinowska, Alicja (Frontiers in Neurology, 2022)
Baló concentric sclerosis (BCS) is a rare demyelinating disorder characterized by acute or subacute neurological symptoms associated with a characteristic lesions of concentric onion skin appearance on MRI images and pathology. The connection between BCS and classic MS is still subject to debate. Our report presents a case of a patient who developed a symptomatic Baló-like lesion following several years of classical relapsing-remitting multiple sclerosis.